Delima Consult Sdn. Bhd: Double-storey bungalow Shah Alam & elevated water tank / Mohamad Amirul Aizat Rashid, Zarith Ashraf Muhammad Tarmizi, Izzah Mardhiah Md Aris - Rashid, Mohamad Amirol Aizat; Muhamad Tarmizi, Zarith Ashraf; Md Aris, Izzah Mardhiah (2016)
The project is designed using Esteem Software where the detailed design of the project is produced. The detailed design includes the structural drawing, the report of the project and the detailing of structural members such as beams, slabs, column and foundation. Before using the software, the manual calculation is done first. The manual calculation is a manual design of each structural members to calculate the load cater by each structural members. Since the load is transfer from top to the bottom structure, we begin our calculation with beam structure. Then we proceed with slab, column and foundation. For this project, calculation of staircase is included given the project is a double-storey house. We also calculate the adequacy of soil fo this project which is important in order to construct a solid and stable house. For this project, we are required to design water tank for the Marine Fish and Shrimp Hatchery Centre located at Merchong, Pahang. The water tank is the elevated type and made of steel. The elevated steel water tank was designed by a nominated architecture from Lembaga Arkitek Malaysia. We are in charge in proposing the detailed design of the project including the drawing of the project and the checking of the specified data such as the sizes of structures the types of structures, the materials used, etc are satisfactory for a solid elevated water tank.